Dyn[n]arenes: Versatile Platforms To Study the Interplay between Covalent and Noncovalent Bonds. Issue 2 (14th January 2022) - Vial, Laurent; Perret, Florent; Leclaire, Julien
Abstract: Dyn[ n ]arenes are the strict polydisulfide‐based analogues of pillar[ n ]arenes. Although less famous than their static homologues, these dynamic cavitands possess unique (stereo)chemical features. The disulfide bridge between monomeric units not only provides these architectures with constitutional lability but is also an additional stereogenic element. As a result, the covalent assembling process can be guided by supramolecular interactions with or without a targeted partner, enabling to decipher supramolecular at work from the synthetic stage. Not only can the size and functions be chosen on demand, but the stereochemical features can be precisely controlled by careful choice on the assembling conditions. Eventually, deciphering the interactions at work during self‐assembly opens the way toward innovative applications such as biomolecules sensing. This account describes the synergistic interplay between covalent and noncovalent bounds found in dyn[ n ]arenes. Abstract : Despite a growing number of reports involving dyn[ n ]arenes, there is still plenty of room for further exciting developments that could result from a better exposure of these cavitands, which is the ambition of this account.